Migration measurement of the cemented Lubinus SP II hip stem - a 10-year follow-up using radiostereometric analysis - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Wiendieck, Kurt; Söder, Stephan; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Wierer, Thomas (Biomedizinische Technik, 2016)
In a previous radiostereometric analysis (RSA) of the Lubinus SP II (Link, Hamburg, Germany), which is one of the most often used cemented hip stems worldwide, our research group detected a very small but statistically significant distal migration of -0.03±0.17 mm 2 years after surgery compared to the postoperative radiograph. Maximum subsidence occurred between 6 and 12 months. The implant appeared to have stabilized after 2 years. The mean value of maximum total point motion (MTPM) was 0.99±0.69 mm, which was detected 2 years after surgery. The purpose of this study was to analyze the migration pattern and to verify the predictive value of short-term RSA of the Lubinus SP II stem after 10 years. After a follow-up of 5 and 10 years, 38 and 27 out of 100 patients remained available for further assessment, respectively. No statistically significant implant translation or rotation was found along or about the axes of the global coordinate system 5 and 10 years after surgery with respect to the postoperative radiograph. Furthermore, the MTPM was stable in both follow-up periods. The results suggest that the Lubinus SP II hip stem is still stable 10 years after surgery, supporting that determining prognosis by short-term RSA follow-up of 2 years could be an appropriate tool for appraisal of implant behavior 10 years after surgery.
EVALuna2:6812

Radiostereometric migration analysis of the Cerafit femoral stem: 28 patients followed for 2 years - Tschunko, Franz; Wagner, Benedikt; Hong, Yutong; Söder, Stephan; Wölfel, Rainer; Müller, Lutz Arne; Forst, Raimund; Sesselmann, Stefan (Biomedizinische Technik, 2015)
Radiostereometric analysis (RSA) is the gold standard evaluating micromovements after total hip arthroplasty. The aim of this study was to investigate the migratory pattern of an uncemented femoral stem during the first 2 years after surgery. We followed 28 patients with a mean age of 57 (SD 13) years for the first two postoperative years. Radiostereometric analysis was used to measure the translation and rotation of the femoral component. The Harris hip score (HHS) was determined to evaluate the clinical outcome. No stem had to be revised. The mean HHS advanced from 35 (SD 11) preoperative to 89 (SD 10) 1 year after surgery. At the end of the observation period, mean subsidence of the stem was 0.26 mm (SD 0.82). Maximum total point motion (MTPM) was 1.23 mm (SD 1.22). The main distal migration took place up to 6 weeks after surgery with nearly no further subsidence up to 2 years postoperatively. All the measured migrations of the hip stem were very small. Results of the HHS demonstrate good clinical outcome. Long-term RSA is necessary to assess possible late migration of the Cerafit standard femoral stem.
EVALuna2:10856

Radiostereometric migration measurement of an uncemented Cerafit® femoral stem: 26 patients followed for 10 years - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Tschunko, Franz (Biomedizinische Technik, 2017)
Radiostereometric analysis (RSA) is the gold standard for evaluating micromotions of orthopaedic implants. The method is applied for identifying novel design weaknesses in endoprostheses. Current research frequently assesses relatively short time periods. Short-term RSA studies have been widely used for predicting the long-term stability of many hip prosthetic designs, but only a few studies have focused on uncemented hip implants, especially for extended periods. The purpose of this study was to analyse the migration pattern of the Cerafit® femoral stem within 10 years and to verify the predictive value of short-term RSA after 2 years for this uncemented femoral hip stem. Twenty-six patients were followed for 10 years. Ten years after implantation, a mean subsidence of 0.22 mm±0.56 mm, a mean internal rotation of 0.59°±1.67° and a mean maximum total point motion (MTPM) of 1.28 mm±0.54 mm were detected. The main migration took place in the first 6 weeks after surgery (subsidence of 0.36 mm±0.73 mm; internal rotation of 0.62°±1.49°, MTPM of 1.05 mm±0.68 mm). All the migration values measured were small. No late-onset migration was observed. This study suggests that the Cerafit® implants are stable after 10 years. Thus, RSA could be the best tool to assess long-term implant behaviour.
EVALuna2:33711